2017
DOI: 10.1016/j.snb.2016.08.092
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol biosensing with a polydopamine-modified nanostructured platinum electrode prepared by oblique angle physical vacuum deposition

Abstract: This paper reports a novel cholesterol biosensor based on nanostructured platinum (Pt) thin films prepared by Magnetron Sputtering (MS) in an oblique angle (OAD) configuration. Pt thin films were deposited onto a gold screen-printed electrode and characterized using Rutherford Back Scattering (RBS), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Cyclic Voltammetry (CV), X-ray Photo-electron Spectroscopy (XPS), Atomic Force Microscopy (AFM) and wetting analysis. Our results confirmed that the film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…The roughness, expressed as Root Mean Square (RMS), presented values of 7.69 nm and 10.30 nm, as deduced from Figure S2a and S2b, respectively. These values agree with the RMS value reported in previous publications for similar configurations . Interestingly, the TOF‐SIM deep profile analysis (see Figure S3) showed that the nanocolumns presented a bilayer structure, with Ni atoms at the bottom of the nanocolumns and Cu atoms on the top, as expected from the preparation method described in the experimental section.…”
Section: Resultssupporting
confidence: 91%
“…The roughness, expressed as Root Mean Square (RMS), presented values of 7.69 nm and 10.30 nm, as deduced from Figure S2a and S2b, respectively. These values agree with the RMS value reported in previous publications for similar configurations . Interestingly, the TOF‐SIM deep profile analysis (see Figure S3) showed that the nanocolumns presented a bilayer structure, with Ni atoms at the bottom of the nanocolumns and Cu atoms on the top, as expected from the preparation method described in the experimental section.…”
Section: Resultssupporting
confidence: 91%
“…in optics, biomedicine, sensors, microfluidics, LED fabrication, etc. [1][2][3][4][5][6][7][8]. These films have been classically deposited by the evaporation technique at glancing angles, which allowed the control of different microstructural features such as specific surface, density, pore distribution, pore connectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of disease biomarkers is extremely important in clinical diagnosis, and much attention has been paid to the development of new technologies to determine early signs of various diseases, , such as enzyme-linked immunosorbent assay, fluorescense methods, , surface plasmon resonance, surface enhanced Raman spectroscopy, and so on. Among these, electrochemical technique has attracted much interest owing to its advantages such as high sensitivity, simple preparation, convenient operation, and low cost. Currently, the sensitivity of electrochemical biosensors can be greatly improved by using signal amplification strategies, but direct detection of targets in real complex media with electrochemical biosensors remains a challenge due to severe nonspecific adsorption.…”
Section: Introductionmentioning
confidence: 99%